Putting placebo‐controlled trials in developing countries to the interpersonal justifiability test. Issue 3 (18th September 2018) - Webb, Jamie
Abstract: This paper considers the ethics of placebo‐controlled trials in developing countries, where a treatment already exists but is not available due to the low local standard of care. Such trials would not be permitted in more developed nations where a higher standard of care is available. I argue that there are moral intuitions against such trials, but a further intuition that if the trials were aimed at producing treatment options for the developing world, that would be more permissible than if the trials were designed with the benefit of rich world people in mind. An approach based upon GA Cohen's work on interpersonal justifiability is suggested to allow us to explain these intuitions. Cohen's framework shows that these trials are ethically problematic because the inequality in healthcare provision between developing and developed nations that allows them to take place is at least partly the pharmaceutical corporations' fault. Following Cohen's argument, this means the trials are non‐comprehensively justified. This allows for a more complete explanation of our intuitions than to consider such trials as cases of exploitation, because intuitions on the ethicacy of research can vary even when the exploitation relation remains the same. It is then established that there is good empirical evidence to believe that pharmaceutical corporations do fail the interpersonal justifiability test. The policy implications of this judgement are then considered, and it is suggested that the framework might be equally applicable to examining the permissibility of research conducted on vulnerable people within more developed nations.